2017
DOI: 10.3390/biomedicines5030038
|View full text |Cite
|
Sign up to set email alerts
|

New Paradigm for a Targeted Cancer Therapeutic Approach: A Short Review on Potential Synergy of Gold Nanoparticles and Cold Atmospheric Plasma

Abstract: Application of Gold nanoparticles and Cold Atmospheric plasma as a targeted therapeutic adjunct has been widely investigated separately in cancer therapy. Gold nanoparticles, with their biocompatibility, lower cytotoxicity and superior efficacy, are becoming substantially more significant in modern cancer therapy. Likewise, cold atmospheric plasma, with rich reactive species including reactive oxygen species (ROS) and reactive nitrogen species (RNS), is being explored to selectively target and kill cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Several studies by others and us have observed plasma-induced tumor cell death before [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. Kumar and colleagues observed in several pancreatic cancer cell lines an increase in apoptosis concomitant with downregulation of MAPK7, BCL2, and CHK1 [99].…”
Section: Discussionmentioning
confidence: 94%
“…Several studies by others and us have observed plasma-induced tumor cell death before [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. Kumar and colleagues observed in several pancreatic cancer cell lines an increase in apoptosis concomitant with downregulation of MAPK7, BCL2, and CHK1 [99].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, prior to the clinical application of CAP, several technical parameters need to be studied in more detail, including penetration depth, optimal dosage, and repetitive applications. Also, recent evidence suggests a potential synergy of nanoparticles in combination with CAP that leads to a maximized targeted efficacy [ 120 ]. At the same time, the killing efficacy of plasma should be tested on chemoresistant cancer cells.…”
Section: Clinical Prospects and Conclusionmentioning
confidence: 99%
“…The excellent stability of GNP stabilized with thiolated ligands permits chemical reactions directly on their surface . The ligands used to stabilize GNP may be specifically chosen for drug encapsulation and release, or to target specific tissues, such as tumors …”
Section: Introductionmentioning
confidence: 99%